Emotional consequences of the COVID-19 pandemic in adolescents: challenges to public health - Thaianne Cristine Gadagnoto; Lise Maria Carvalho Mendes; Juliana Cristina dos Santos Monteiro; Flávia Azevedo Gomes-Sponholz; Nayara Gonçalves Barbosa (Revista da Escola de Enfermagem da USP, 2022)
Abstract Objective: To describe adolescents’ everyday activities and emotional consequences related to the COVID-19 pandemic. Method: Qualitative study grounded in Alfred Schütz’s social phenomenology, involving 22 students at two public schools in a municipality in the state of São Paulo, Brazil. Interviews were conducted, had their audio recorded, and were analyzed according to a thematic categorization. Results: Five categories emerged from the accounts: i) adolescents’ reaction before the COVID-19 pandemic; ii) emotional consequences; iii) concern about the family; iv) adolescents’ adaptation; and v) fragmentation of social support networks. Feelings such as uncertainty, fear, anguish, anxiety, and lack of motivation, depressive symptoms, and extreme suicidal ideation were reported. Conclusion: Paying attention to adolescents’ psychosocial needs is essential, especially in face of the possibility of post-traumatic stress as a result of the COVID-19 pandemic. Health professionals’ technical competence combined with sensibility, strengthening of social support networks, and engagement of different community sectors are fundamental for promoting adolescent mental health in the current transition and resignification period following the COVID-19 pandemic.